2000
DOI: 10.1258/0022215001906697
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective survey of long-term results and patient satisfaction with uvulopalatopharyngoplasty for snoring

Abstract: The aim of this study was to retrospectively survey patients who had undergone the uvulopalatopharyngoplasty (UPPP) operation over a two-year period, assessing loudness of snoring, sleep quality and patient satisfaction. A total of 271 patients were sent questionnaires to assess snoring and sleeping habits, with additional questions about pain and satisfaction with surgery. Those who did not reply were contacted by telephone. Seventy-four per cent of the target population were surveyed. Taking an improvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 7 publications
3
40
0
5
Order By: Relevance
“…As a consequence, rhonchopathy and its associated symptoms can be permanently eliminated or substantially decreased in the majority of cases. Patient satisfaction of 75% in our series is within the upper range of 49% [17] to 86% [26] reported in the literature. Besides the inadequate reduction of snoring and postoperative pain, Hicklin et al [17] reported postoperative complications as a particular reason for low patient satisfaction [49%].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As a consequence, rhonchopathy and its associated symptoms can be permanently eliminated or substantially decreased in the majority of cases. Patient satisfaction of 75% in our series is within the upper range of 49% [17] to 86% [26] reported in the literature. Besides the inadequate reduction of snoring and postoperative pain, Hicklin et al [17] reported postoperative complications as a particular reason for low patient satisfaction [49%].…”
Section: Discussionsupporting
confidence: 81%
“…Literature data on this is contradictory: Larson et al [18], Verse et al [19] and Hicklin et al [17], but not Boot et al [20] reported an effect of body weight on the results of UPPP. It remains controversial whether the decrease in weight results because of normalization of sleep, daytime sleepiness and appetite or whether the decrease in weight causes less rhonchopathy independently of the UPPP.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Surgical interventions, which may be considered when less invasive measures have failed, carry the risk of potential complications, and the overall long-term success rate is no more than 50% [9,10]. For many patients with sleepdisordered breathing, especially those with significant simple snoring (apnoea-hypopnoea index <10), there exists no treatment option that is effective, acceptable and justifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous approaches to find an adequate surgical treatment for primary snoring, no gold standard exists. Various kinds of surgical procedures are available, most of which have been developed for the treatment of obstructive sleep apnea (OSA): uvulopalatopharyngoplasty [7,8], tonsillectomy [9], laser-assisted uvulopalatoplasty [10], uvulaflap [11,12], soft palate implants [13], or radiofrequency surgery of the tongue base or the soft palate [14][15][16][17][18][19]. Some of these procedures are rather invasive and connected with side effects such as post-operative pain or bleeding or persistent swallowing difficulties [20], whereas others show only moderate efficacy [19].…”
Section: Introductionmentioning
confidence: 99%